The Role Of Notaries In The Process Of Establishing A Limited Liability Company Legal Entity In Indonesia - Muhammad Arief Rakhman Hakim; Abdul Rokhim; Sunardi (PALAR | PAKUAN LAW REVIEW, 2026)
The development of economic globalization requires legal certainty in the establishment of business entities, especially Limited Liability Companies (PT), which makes the role of notaries increasingly strategic in ensuring legality and transparency. The problem in this study is how the authority, responsibility, and role of notaries in the process of establishing a Limited Liability Company based on laws and regulations, as well as their implications for the principles of transparency and legal certainty. The purpose of this research is to analyze in depth the authority, responsibility, and role of notaries in the establishment of a PT, especially in relation to the identification of beneficial owners and the preparation of the Articles of Association. This type of research is a normative legal research that is descriptive-analytical, using secondary data obtained through library research, and analyzed qualitatively with a legislative and conceptual approach. The results of the study show that the authority of notaries has developed from an administrative function to a preventive function in ensuring legal transparency. The notary's responsibilities are not only limited to formal truthfulness, but also face expansion due to the obligation to identify beneficial owners, which raises potential conflicts with the principle of office secrecy. In addition, notaries have a strategic role in the preparation of the Articles of Association as legal drafters and advisors. Thus, notaries play an important role in supporting legal certainty and good corporate governance in Indonesia. Keywords: Notary; Limited Liability Companies; Notary Authority; Notary Responsibility; Beneficial Owners.